Molecular detection of Enterobacter hormaechei in bovine respiratory disease - HAJ Gharban (Veterinární Medicína)
Bovine respiratory disease (BRD) develops from complex interactions among environmental, host and pathogenic factors. This study aimed to phenotypically identify Enterobacter hormaechei isolated from cattle with BRD and assess antimicrobial susceptibility and determining the molecular phylogeny of local E. hormaechei strains. Between November 2023 and March 2024, nasal swabs were collected from 93 cattle with BRD, before culturing for phenotypic analysis, and performing the polymerase chain reaction (PCR) for molecular characterisation. Of the 93 samples evaluated, 15.79% and 24.56% tested positive for E. hormaechei isolates on culture and PCR, respectively. The local isolates exhibited high resistance to amoxicillin, ampicillin, amikacin, nalidixic acid and ceftazidime; high susceptibility to azithromycin, levofloxacin, gentamicin, ofloxacin, cefepime, ceftriaxone, cefotaxime, nitrofurantoin, ceftazidime and ciprofloxacin; and moderate susceptibility to ciprofloxacin, colistin, imipenem and meropenem. Multiple sequence alignment, phylogenetic tree analysis and homology sequence identification, showed that the five positive isolates were similar to the reference isolate. To the best of our knowledge, this is the first time that E. hormaechei has been isolated in cattle with BRD in Iraq. Because phenotype-based assays show limited accuracy to identify species, we recommend molecular and phylogenetic analysis be included in all similar studies in the future.